1997
DOI: 10.1177/002215549704501002
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Secretion, Degradation, and Fate of Ameloblastin During the Matrix Formation Stage of the Rat Incisor as Shown by Immunocytochemistry and Immunochemistry Using Region-specific Antibodies

Abstract: SUMMARY Rat ameloblastin is a recently cloned tooth-specific enamel matrix protein containing 422 amino acid residues. We investigated the expression of this protein during the matrix formation stage of the rat incisor immunohistochemically and immunochemically, using anti-synthetic peptide antibodies that recognize residues 27-47 (Nt), 98-107 (M-1), 224-232 (M-2), 386-399 (M-3), and 406-419 (Ct) of ameloblastin. Immunohistochemical preparations using antibodies Nt and M-1 stained the Golgi apparatus and secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(95 citation statements)
references
References 33 publications
4
91
0
Order By: Relevance
“…9,14 In the present study, we partially sequenced the amino acids of the major amyloid protein of canine APOT and compared the amino-terminal sequence with that of the enamel proteins rat ameloblastin and porcine sheathlin, which are transcribed in cells of the epithelial root sheath in normal incisor tooth germ. 16,47,48,50 We examined the immunohistochemical profile of the amyloid using antibodies to ameloblastin, sheathlin, amelogenin, and amyloid protein isolated from a canine APOT. …”
mentioning
confidence: 99%
“…9,14 In the present study, we partially sequenced the amino acids of the major amyloid protein of canine APOT and compared the amino-terminal sequence with that of the enamel proteins rat ameloblastin and porcine sheathlin, which are transcribed in cells of the epithelial root sheath in normal incisor tooth germ. 16,47,48,50 We examined the immunohistochemical profile of the amyloid using antibodies to ameloblastin, sheathlin, amelogenin, and amyloid protein isolated from a canine APOT. …”
mentioning
confidence: 99%
“…Both newly secreted matrix proteins present at the forming surface of the enamel layer and partially degraded molecular forms located deeper into it can be concentrated at, or relatively missing from, specific sites within the layer (Smith et al 1989a,b;Kogaya 1994;Nanci et al 1996;Murakami et al 1997;Uchida et al 1991aUchida et al ,b,1997. The most dramatic differences in intraenamel protein concentrations have been observed for nonamelogenins such as ameloblastin and enamelin, for which newly secreted forms are present in high concentration at the enamel surface near ameloblasts (Hu et al 1997a,b;Murakami et al 1997;Uchida et al 1997).…”
mentioning
confidence: 99%
“…The purpose of this investigation was to obtain information about the intracellular and extracellular distribution of ameloblastin vs amelogenin using qualitative and quantitative high-resolution immunocytochemistry in combination with immunoblotting and polyclonal antibodies against the full-length and an internal portion of recombinant ameloblastin, in contrast to synthetic peptide antibodies as was employed in a recent study reported by Uchida et al (1997). Another objective was to clarify issues about sites of expression vs sites of secretion for ameloblastin.…”
mentioning
confidence: 99%
“…On the other hand, enamel matrix proteins are distinctively less glycosylated. Sugar residues are mainly present on non-amelogenins and are predominately N -linked in the case of enamelin (Fukae et al 1996;Hu et al 1998) and a 65-kD sulfated enamel protein , and O -linked in the case of ameloblastin (Cerny et al 1996;Krebsbach et al 1996;Hu et al 1997;Uchida et al 1997;Nanci and Smith 2000). However, a highly glycosylated BL forms at the interface between ameloblasts and enamel at the start of the maturation stage of amelogenesis (Nanci et al 1993).…”
Section: Discussionmentioning
confidence: 99%